Numerical simulation of blood fluid in hemodialysis catheters and its thrombogenic potential (Acta Scientiarum. Health Sciences, 2019)
Purpose: To numerically simulate blood flow within central venous catheters of hemodialysis and its thrombogenic potential. Methods: Numerical simulation research performed through the dynamic computational program of fluids. A three-dimensional geometry of right and left internal jugular veins were built, taken from the Visible Human Project®. Catheters with obstructed and unobstructed lateral holes were constructed. For the simulation, we considered the duration of the cardiac cycle of 0.8 s with pulsatile cycle of 75 beats per minute. Results: Shear stress, velocity and pressure increased when the catheter was within the vein and when they were obstructed. At the venous orifice of the catheter that was unobstructed, the velocity increased from 0.99±0.02m/s to 1.79±0.009 m/s and the pressure from 1487±0.8Pa to 3215±0.7Pa. Blood re-circulation areas have created areas of stagnation of blood flow, making it more susceptible to the development of venous thrombi. Conclusion: This study may contribute to the expansion of multiprofessional partnerships between health professionals and Bioengineering fields in order to research health problems that can be verified through advanced technologies. Such technologies, such as simulation programs, detail possible adverse events based on scientific evidence that often happen silently in patients